KEBIJAKAN FISKAL DALAM ISLAM (Solusi Bagi Ketimpangan dan Ketidakadilan Distribusi) - Rasiam, Rasiam (The Pontianak State Institute of Islamic Studies, 2014)
The Fiscal policy is a government policy that deals with the state revenues and expenditures. In a more understandable term, it means that the Government regulates financial affairs for the survival of the country, especially in the economic sphere. In the fiscal policy, there are two important things to note, i.e. the income and expenditures. The Government should increase revenue so the country can finance all its needs, while at the same time can also apply efficiency. In Islam there is fixed income that has already become a provision such as the zakat, waqf, Jizya, amwal fadhla, nawaib, kafarat, kharaj and ushr each with its designated distribution. From the perspective of the goal, there is no difference between fiscal in general and that in Islam. It is just that in Islam in addition to the regulation of the Government, it is also a religious obligation such as the expenditures for infaq, sadawah and waqf.